PENGARUH KUALITAS LAYANAN DAN MANAJEMEN FARMASI TERHADAP KEPUTUSAN BELI ULANG OBAT PASIEN RAWAT JALAN DI RUMAH SAKIT LABUANG BAJI MAKASSAR - Hastuti Hanisu; Indar Indar; Muhammad Rum (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2021)
This study aims to analyze the influence of quality of pharmaceutical services and management on the decision to repur purchase outpatient medicines at the Pharmaceutical Installation of Labuang Baji Makassar Hospital in 2019. The research was conducted at Labuang Baji Makassar Hospital which began with a survey first until the research in February 2020. The population in the study was patients (Non BPJS / KIS) re-buyers in the Pharmaceutical Installation of RS Labuang Baji Makassar in February 2020 and the sample in this study amounted to 60 0rang Analysis method used in this study is a quantitative descriptive method, with double regression testing preceded by conducting validity and reliability tests of each variable question items as well as assumption tests. The results of this study show that: 1) Officer-friendly attitude has a significant positive influence on the decision to re-buy at the pharmacy Labuang Baji Hospital, 2) The completeness of the prescription has a significant positive influence on the decision to re-buy at the pharmacy Labuang Baji Hospital, 3) The price of the drug has an insignificant negative influence on the decision to re-buy at the pharmacy Labuang Baji Hospital , 4) Drug safety information has a significant positive influence on the decision to re-buy at the pharmacy Labuang Baji Hospital, 5) Drug safety information has a dominant effect on the buyback decision. This finding is in accordance with the results of the study at the Outpatient Installation Pharmacy of Labuang Baji Hospital Makassar. Keywords : Quality of Service, Pharmaceutical Management, Drug Buyback Decision